An Influence of the Hindi Language on Daladi Dialect of Konkan: A Linguistic Study: कोकण की दालदी बोलीभाषा पर हिंदी का प्रभाव: एक भाषाशास्त्रीय अध्ययन - Madhale, Shahu Dasharath (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
This research paper presents an in-depth linguistic analysis of the growing influence of the Hindi language on the Daldī language spoken in the Konkan region. Daldī, an Indo-Aryan language, is primarily spoken by the Konkani Muslim community in Maharashtra and Goa. The main objective of this study is to examine the nature and extent of this influence in the context of socio-cultural factors such as media, education, and economic migration. Based on a qualitative research methodology, the study collected data through fieldwork, in-depth interviews, and observation. The findings reveal that the influence of Hindi is evident at all levels of the Daldī language. At the lexical level, large-scale borrowing of Hindi words is the most prominent outcome. At the phonological level, Hindi vowels and consonant sounds are blending into Daldī pronunciation. The most profound impact is seen at the grammatical level, where Hindi verb forms and case markers are replacing corresponding Daldī structures. Due to Hindi’s growing national reach, media dominance, and academic importance, regional languages like Daldī are undergoing linguistic restructuring. The purpose of this study is to understand the nature, scope, and direction of this influence and to explore its socio-cultural implications. Abstract in Hindi Language: कोकण क्षेत्र में बोली जाने वाली दालदी भाषा पर हिंदी भाषा के बढ़ते प्रभाव का एक गहन भाषाशास्त्रीय विश्लेषण यह शोध पत्र प्रस्तुत करता है। दालदी, एक इंडो-आर्यन भाषा, जो मुख्यतः महाराष्ट्र और गोवा के कोकणी मुस्लिम समुदाय द्वारा बोली जाती है। इस अध्ययन का प्राथमिक उद्देश्य मीडिया, शिक्षा, और आर्थिक प्रवास जैसे सामाजिक-सांस्कृतिक कारकों के परिप्रेक्ष्य में इस प्रभाव की प्रकृति और सीमा की जाँच करना है। गुणात्मक शोध पद्धति पर आधारित, इस अध्ययन ने क्षेत्र-कार्य, गहन साक्षात्कार और प्रेक्षण के माध्यम से आँकड़ों का संग्रह किया। निष्कर्ष बताते हैं कि हिंदी का प्रभाव दालदी भाषा के सभी स्तरों पर स्पष्ट है। शब्दावली स्तर पर, हिंदी शब्दों का बड़े पैमाने पर उधार सबसे प्रमुख परिणाम है। ध्वनि स्तर पर, हिंदी के स्वर और व्यंजन ध्वनियाँ दालदी उच्चारण में घुल रही हैं। सबसे गहरा प्रभाव व्याकरण के स्तर पर देखा गया है, जहाँ दालदी के क्रिया रूपों और कारक चिह्नों का स्थान हिंदी के समरूप तत्व ले रहे हैं। हिंदी, राष्ट्रीय स्तर पर अपनी बढ़ती पहुँच, मीडिया के प्रभुत्व और शैक्षणिक महत्व के कारण, दालदी जैसी क्षेत्रीय भाषाओं के भाषाई ढाँचे को पुनः आकार दे रही है। इस अध्ययन का उद्देश्य इस प्रभाव की प्रकृति, सीमा और दिशा को समझना है तथा इसके सामाजिक-सांस्कृतिक निहितार्थों की पड़ताल करना है। Keywords: दालदी भाषा, हिंदी भाषा का प्रभाव, भाषाशास्त्रीय अध्ययन, कोकण क्षेत्र, भाषाई परिवर्तन, भाषाई स्थानांतरण, सांस्कृतिक पहचान